Postcardiotomy ECMO Support after High‐risk Operations in Adult Congenital Heart Disease. (20th July 2016) - Acheampong, Benjamin; Johnson, Jonathan N.; Stulak, John M.; Dearani, Joseph A.; Kushwaha, Sudhir S.; Daly, Richard C.; Haile, Dawit T.; Schears, Gregory J.
Abstract: Background: Cardiac operations in high‐risk adult congenital heart disease (ACHD) patients may require mechanical circulatory support (MCS), such as extracorporeal membrane oxygenation (ECMO) or intraaortic balloon pump (IABP), to allow the cardiopulmonary system to recover. Methods: We reviewed records for all ACHD patients who required MCS following cardiotomy at our institution from 1/2001 to 12/2013. Results: During the study period, 2264 (mean age 39.1 years, females ∼54.1%) operations were performed in ACHD patients of whom 24 (1.1%) required postoperative MCS (14 males; median age 41 years, range 22–75). Preoperatively the 24 patients had a mean systemic ventricular ejection fraction of 47% (range 10–66%); 72% of these patients were in NYHA class III/IV heart failure. The common underlying diagnoses included pulmonary atresia with intact ventricular septum (20%), tetralogy of Fallot (16%), Ebstein anomaly (12%), cc‐TGA (12%), septal defects (12%), and others (28%). Operations performed were valvular operations with/without maze (58.2%), Fontan conversion (21%), coronary bypass grafting with valvular operations (12.5%), and heart transplant (8.3%). Indications for MCS were left‐sided (systemic) heart failure (32%), right‐sided (subpulmonary) heart failure (24%), biventricular heart failure (36%), persistent arrhythmia (4%), and hypoxemia (4%). Forty‐two percent were placed on ECMO only; in the second group, IABP was attempted and subsequently followed by ECMO initiation. The mean duration of MCS was 8.4 days (range 0.8–35.4). Common morbidities included coagulopathy (60%), renal failure (56%), and arrhythmia (48%). Overall, 46% of patients survived to hospital discharge. Deaths were due to either multi organ failure or the underlying cardiac disease; sepsis was the primary cause of death in one patient. Median follow‐up for survivors was 41 months (maximum 106 months). NYHA functional class was I/II in all 8 late survivors. Conclusions: Following complex operations in high‐risk ACHD patients, MCS may be required. Despite significant morbidity, nearly half of patients survive to hospital discharge.